2019
DOI: 10.1007/s00335-019-09816-1
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic gene expression variations in response to high-fat diet-induced impaired glucose tolerance using RNAseq analysis in collaborative cross mouse population

Abstract: Hepatic gene expression is known to differ between healthy and type 2 diabetes conditions. Identifying these variations will provide better knowledge to the development of gene-targeted therapies. The aim of this study is to assess diet-induced hepatic gene expression of susceptible versus resistant CC lines to T2D development. Next-generation RNA-sequencing was performed for 84 livers of diabetic and non-diabetic mice of 41 different CC lines (both sexes) following 12 weeks on high-fat diet (42% fat). Data an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Nox4 was shown to be downregulated in females. Another liver specific study of Abu-Toamih confirmed downregulation of Nox4 in females [ 37 ] ( Table 1 ). This study additionally described higher Lepr expression in female mice.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Nox4 was shown to be downregulated in females. Another liver specific study of Abu-Toamih confirmed downregulation of Nox4 in females [ 37 ] ( Table 1 ). This study additionally described higher Lepr expression in female mice.…”
Section: Resultsmentioning
confidence: 87%
“…To validate the data regarding gender differences we examined two studies about gender differences in hepatic tissue. A study of Lau-Corona et al comparing gender specific effects in liver tissue [ 36 , 37 ] showed sex specific differences in glutathion-S-transferases, Nox2 and Nox4 ( Table 1 ). Nox4 was shown to be downregulated in females.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the CC lines exhibited tremendous variation in glucose sensibility, body weight gain and polyp counts. We believe that by using this genetic reference population and expanding the number of the lines studied to 30 or more and using genome‐wide association studies (GWAS), we will be able to identify modifier genes associated with the multimorbidity of these diseases , as was successfully achieved in our previous studies 12,14‐20,22,34‐36 …”
Section: Discussionmentioning
confidence: 87%
“…The sex bias of hepatic gene expression has also been described in several inbred mouse strains [8,10,55]. Underlying mechanisms for genetically-based differences between strains are poorly understood [49,[56][57][58][59], primarily because most studies of sex bias in mouse liver have focused on strains of primarily M. m. domesticus genetic background (i.e., CD-1 and C57BL/ 6J) and did not include wild-derived strains.…”
Section: Introductionmentioning
confidence: 99%